2018
DOI: 10.2174/1872214812666180508144513
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Management of the Child with Hypothyroidism

Abstract: Ahead of Print article withdrawn by publisher.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 0 publications
0
12
0
4
Order By: Relevance
“…Twenty children were excluded from the study because of several reasons: certain syndromes (3), anatomical disorders in head and neck (4), cerebral palsy (8), and autism or mental retardation (5). Thus, 89 children were available for further analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty children were excluded from the study because of several reasons: certain syndromes (3), anatomical disorders in head and neck (4), cerebral palsy (8), and autism or mental retardation (5). Thus, 89 children were available for further analysis.…”
Section: Resultsmentioning
confidence: 99%
“…4 Every child with speech delay should undergo hearing test to prove whether there is any hearing disorder or not. 5 The gold standard hearing tests are otoacustic emission (OAE) and brainstem evoked response audiometry (BERA). These objective tests have high sensitivity and specificity in detecting the presence of hearing loss in children, but expensive.…”
mentioning
confidence: 99%
“…[1] It has been suggested that bilingual children can use both languages effectively generally when they reach to 5 years of age. [37,38] We could not encounter any descriptive study in the literature which analyzed distribution of psychiatric diagnoses, sociodemographic characteristics, and virtual (TV) exposure in children with speech delay in children in our country. Therefore, this study is the first of its kind.…”
Section: Discussionmentioning
confidence: 99%
“…Diperkirakan 5%10% anak mengalami masalah keterlambatan perkembangan. 13 Keterlambatan perkembangan umum merupakan bagian dari keterlambatan perkembangan, dengan prevalensi 1%3%. 3 Penyebab keterlambatan perkembangan umum yang terbanyak adalah kelainan kromosom dan malformasi otak, tetapi banyak juga penyebab lainnya.…”
Section: Hasilunclassified
“…Keterlambatan bicara dapat merupakan gejala dari berbagai penyakit seperti retardasi mental, kelainan pada pendengaran, gangguan dalam berbahasa, autis, afasia, dan keterlambatan dalam perkembangan. 13,14 Dalam pemeriksaan anak dengan keluhan gangguan bicara diharapkan dokter juga memeriksa perkembangan kognitif, neurologis, fisik serta perkembangan anak lainnya. Hal tersebut sangat penting karena gangguan bicara dapat bersifat sekunder dari kelainan perkembangan lainnya atau bersamaan dengan kelainan lain.…”
Section: Hasilunclassified